A compact dual‐functional component for spatial diversity and multiplexing applications. Issue 3 (2nd December 2021) - Sun, Li; Zhou, Shi‐gang; Zhang, Guan‐xi; Sun, Bao‐hua
Abstract: This paper presents a new compact four‐port component with dual‐functional dual‐mode characteristics for spatial diversity and multiplexing applications. The component can achieve the 3‐dB hybrid coupler mode at the lower frequency and the transmission line mode at the higher frequency, corresponding to spatial diversity and multiplexing applications, respectively. The proposed component is designed based on a three‐section crossover and analyzed based on the Even‐odd model analysis. It features good S ‐parameter characteristics, compact size, and none of the RF switches. A component working at 4.5‐/5.4‐GHz has been fabricated and measured to prove its design theory. To practice, the proposed component is applied to a 1 × 2 wideband Yagi antenna array. The measured results show diversity beams and multiplexing beams at two operating bands respectively, suitable for complex wireless communication systems.